Implementasi Model Pembelajaran Kooperatif Berbantuan Mind Map Untuk Meningkatkan Hasil Belajar PKN Siswa Kelas IX 2 SMP Negeri 5 Dumai Tahun Pembelajaran 2011/2012 - Hartini Hartini (PAKAR Pendidikan, 2014)
The purpose of this research is increasing PKn studying report with Mind Map cooperative learning model for IX.2 grade SMP Negeri 5 Dumai. The changing aim variable in this research is PKn studying report, meanwhile the action variable is Mind Map cooperative learning. The form of the research is action research class using cycle model that contain 2 cycles. Each cycles contain 4 steps, there are planning, action, observation and reflection. 40 students of IX.2 grade SMP Negeri 5 Dumai as a subject there are 12 boys and 28 girls. Collecting data methods are test, observation, and documentation. Analysis data method is descriptive analysis. Based on researching result, we can say that there is an increasing result after doing class action using Mind Map cooperative learning model for PKn subject. It can be shown in students’ frequency before and after action class to the students is increase. Cycle I shows the increasing of PKn subject with classical percentage that is 77,5% or 31 students. On cycle II shows the increasing PKn subject that reach average score (KKM) is about 95% or 38 students.